Health Status of Broiler Chickens Fed Diets Containing Palm Kernel Cake with Enzyme Mixture Supplementation - Zubaidah, S.; Ariyadi, B.; Hanim, C.; Baskara, A. P.; Zuprizal (Tropical Animal Science Journal, 2024)
Palm kernel cake (PKC) utilization as poultry feed has limitations due to its high crude fiber and non-starch polysaccharides, which make it difficult for poultry to digest. This study aimed to determine the effect of enzyme supplementation on blood profile, gastrointestinal health, and intestine histomorphology of broiler chickens fed PKC. This study used 1,080 Indian River strain roosters and two kinds of enzyme mixtures. Enzyme 1 consisted of mannanase 182 g/ton, NSPase 200 g/ton, and protease 130 g/ton, and Enzyme 2 consisted of mannanase 182 g/ton, NSPase 400 g/ton, and protease 260 g/ton. This study used six treatments and six replicates, and each replicate consisted of 30 birds. Data were analyzed using a completely randomized design with a factorial pattern of 2 × 3 and 6 replications. The treatment of factor A consisted of 3 levels of enzyme addition (No enzyme, Enzyme 1, and Enzyme 2), and factor B consisted of 2 levels of PKC (10% and 20%). The data obtained was analyzed using analysis of variance (ANOVA), and the significant difference among treatments was further analyzed using Duncan’s multiple range test. The experimental broilers fed PKC supplemented with enzyme had increased (p<0.05) villus height in the duodenum and ileum and decreased (p<0.05) relative weight percentage of the ventriculus (A2B1 and A3B1). The PKC supplementation increased (p<0.05) the relative weight percentage of proventriculus, duodenum, ileum, caecum, pH of ileum, crypta depth in the duodenum and ileum, but decreased (p<0.05) villus height in the jejunum. Enzyme supplementation increased (p<0.05) the plasma albumin, pH of duodenum, and villus width, but decreased crypta depth in the duodenum. This research concluded that Indian River strain roosters fed ration with 10% PKC supplemented with mannase, NPSase, and protease at doses of 182 g/ton, 200 g/ton, and 130 g/ton had the best health status.